تبیین تسهیل کننده ها و موانع شرکت در نماز جماعت از دیدگاه دانشجویان دانشگاه علوم پزشکی اراک؛ یک مطالعه کیفی. - علی جدیدی; میترا جرس; بهمن توان; سلیمان زند (Arak Medical University Journal)
Introduction: Prayer is one of the most important manifestations of the spirit of monotheism in life. Despite the importance of prayer in life, it seems that according to the number of students in Arak University of Medical Sciences, their participation in congregational prayer is not very strong. Therefore, this study was conducted with the aim of explaining the obstacles to participating in congregational prayers from the perspective of Arak University of Medical Sciences students. Methods: This study is a qualitative research in which data collection was conducted by a trained and informed researcher in a semi-structured manner using a number of guiding questions. Ten students with different academic backgrounds participated in this study. After obtaining consent from the participants to record the interview, they were asked to describe the personal, family, cultural, social, political, and educational challenges of participating in congregational prayers. After the data reached saturation and the researchers realized that no new data was obtained, they terminated the interviews and proceeded to transcribed the interview transcripts. After transcoding, data analysis was performed using content analysis and main concepts were extracted. Qualitative content analysis, which is a common method in qualitative studies, was used in this study. A conventional approach was used to analyze the data. Results: In this study, 10 students from different fields of study (nursing, medicine, radiotherapy, midwifery, anesthesia, surgical technology, nutrition, laboratory science, occupational health) with an average age of 20.6 years participated, of which 5 were male and the rest were female. After analyzing the interviews, a total of 232 codes, 11 subcategories and 2 main categories were obtained, barriers (environmental, nature of congregational prayer, media, cognitive, political, health, welfare, individual and family, cultural and religious) and facilitators (individual characteristics, personality characteristics of the imam). Conclusions: According to the results of this study, by removing the interference between the time of the educational classes and the time of the congregational prayer, expanding the cultural activities of the cultural affairs trustees of the university in order to explain the place of prayer to the students, providing a suitable environment to increase the attendance of officials, professors and Faculty staff, finding ways to increase motivation in graduate students, using continuous religious propaganda at the university level, and encouraging and appreciating active students and staff in performing this divine duty can have a significant impact on the establishment of congregational prayers.